The Importance of High Distress Tolerance in the Relationship between Nonsuicidal Self‐Injury and Suicide Potential. Issue 6 (15th July 2013) - Anestis, Michael D.; Knorr, Anne C.; Tull, Matthew T.; Lavender, Jason M.; Gratz, Kim L.
<x xml:space="preserve">Abstract</x> Research has indicated that nonsuicidal self‐injury (NSSI) and suicidal behavior are strongly related to one another, with a sizable portion of individuals with a history of NSSI also reporting a history of nonlethal suicide attempts. Nonetheless, little research has examined possible moderators of this relationship. One potentially important construct is distress tolerance (DT), which has been shown to be negatively associated with NSSI and positively associated with the acquired capability for suicide. In this study, 93 adult inpatients (54.8% male) receiving treatment for substance use disorders completed a structured interview assessing prior suicidal behavior and questionnaires assessing DT, NSSI, and psychopathology. Results indicated that DT moderates the relationship between NSSI frequency (but not number of NSSI methods) and suicide potential (a continuum ranging from no prior suicidal behavior to suicidal behavior with minimal bodily harm to highly lethal suicidal behavior), ΔR2 = .04; p < .023; f2 = .06, with this relation increasing in strength at higher levels of DT. These results are consistent with an emerging line of research indicating that high levels of DT facilitate suicidal behavior in at‐risk populations and suggest that the capacity to tolerate aversive physiological and affective arousal might be vital to engagement in serious or lethal suicidal behavior.